Accounting information system as a mechanism for human resources is a modelGroup-management in the sports media organization - BENSIRADJ, Imane; SEBTI, Ismail; BENDAKFEL, Kamel (sports creativity, 2025)
This study aims to shed light on the importance of the accounting information system in human resource management in general and the role of the accounting information system within the sports media organization in particular, Where It was found through this study that the institution’s reliance on the accounting information system to measure human resource costs is not sufficient to effectively manage human resources, because the sports media institution in question has also allocated sufficient internal legal texts that clarify the rights and duties of all human resources working in it, on the one hand, On the other hand, it became clear that the management of the beIN SPORTS Group falls into some obstacles when dealing with the costs of human resources, As we find that the tax administration does not recognize the provisions that make up the workers, while the accounting information system requires it to do so, In such cases of inconsistency, the right is given to the tax law, which reduces human resource costs and increases the tax base and deferred taxes the liability for managing the beIN SPORTS group. Keywords: Accounting information